Análisis de los hábitos comunicacionales en el desarrollo del pensamiento crítico con adolescentes del Sector Unidos Para El Triunfo – cantón Quevedo, año 2021 - Macías Anchundia, Cristhian Andrés (2021)
This research was carried out in the city of Quevedo, in the “Unidos para el Triunfo”, where the main objective is to determine how communication habits affect the development of critical thinking in adolescents in the sector. With the practice of communication habits, an increase in the development of critical thinking of adolescents is generated, which allows them to have a better development in each area of their life, reach a higher level of criticality to solve the questions of the day to day. To develop this project, everything related to the two study variables was investigated, obtaining a better explanation of what the subject is about. To prepare the case study, we used the preparation of an online survey applied through an instrument developed in Google forms, in order to collect as much information as possible and find out if these habits are being applied in the lives of adolescents. The results of the application of the survey to adolescents in the sector determined that a third of the adolescents surveyed do not know what communication habits are, so it is essential to promote the practice of these habits, according to that a plan was developed online training so that young people have knowledge about the issue raised.